Masker: Pendekatan Konseling Pastoral di Era Pandemi - Imanuel Teguh Harisantoso (Jurnal Teologi Berita Hidup, 2022)
In the pandemic era, maskers, face shield and handsanitizer are common in society. These health protocols present difficulties in relating to others, but this study looks at the above in a different way. Research with this library approach and descriptive method helps researchers to see the phenomenon of maskers positively and then construct them in a pastoral counseling perspective. This study looked at maskers that originally presented their own hassles in relating to others; become a barrier in building togetherness, communio with others, especially supported by the government's call to keep distance, stay away from crowds and reduce mobility; into a new approach to practical counseling. Maskers provide comfort, tranquility, and hope for a better life for users and others around them. With a maskers, the counselor can ensure himself to be present, related, and build communion with the counsellor and at the same time convince himself that he is called by God to proclaim salvation. Maskers can enlivening one’s mid  from anxiety by a pandemic; ensure acceptance of others, even if they are indicated infectious diseases; joy and volunteering in performing service duties; enable people to ally oneself and cooperate; strengthen the alliance and continue to lead people to reflect on their actions. Maskers bring new hope and new approach in carrying out pastoral counseling functions.